DNA methylation valley as a distinguishing feature occurs in root-specific expressed nicotine-related genes in Nicotiana attenuata - Tong, Ahui; Wang, Bingwu; Wu, Jinsong (Frontiers in Plant Science, 2025)
IntroductionNicotine, the main defense alkaloid of Nicotiana species, is synthesized exclusively in the roots. Several studies have shown that changes in DNA methylation patterns are associated with altered expression of genes involved in the biosynthesis of some secondary metabolites. It remains unknown whether DNA methylation pattern of nicotine-related genes differs in root and leaf tissues. We performed RNA sequencing, quantitative real time PCR and whole-genome bisulfite sequencing of Nicotiana attenuata root and leaf samples to investigate the DNA methylation patterns of root-specific expressed nicotine-related genes.Results and discussionWe found that most of the nicotine-related genes were exclusively and highly expressed in the root, while their DNA methylation patterns were very similar in both tissues. Interestingly, these genes with root-specific expression share a prominent DNA methylation valley (DMV) as a distinguishing feature. Further analysis revealed that 37.4% of the root-preferentially expressed genes were DMV genes, suggesting that root-specific expressed genes, including these nicotine-related genes, were strongly associated with DMV. Our results revealed that having a DMV is a common feature of most nicotine-related genes that are expressed only in the root. Thus, our results provide new insights into the regulation of alkaloid biosynthesis by epigenetic modification.